The Relationship between Job Satisfaction and Work-Life Balance of Non-standard Employment (NSE) Workers of a Manpower Agency - Lagrana, Lyka R.; Bayoneta, Ma. Johanna Ann R. (Philippine Social Science Journal, 2021)
The rapid growth of industrialization and diversification worldwide diverted the trend in the labor market to be shifted towards alternative work arrangements, also known as Non-standard Employment (NSE). In the Philippines, these alternative forms of employment of NSE can be greatly observed. The majority of workers under NSE arrangements fall under fixed-term or contractual employees. The purpose of this study is to assess the level of job satisfaction and work-life balance of the NSE workers of a manpower agency in a highly urbanized city in the Philippines and explore their challenges. Moreover, it sought to determine the significant relationship between job satisfaction and work-life balance. Using a standardized questionnaire, the data were gathered from a sample of 282 agency workers. The study tested hypotheses using Mann Whitney U test, Kruskal Wallis, and Spearman rank. The results showed that workers demonstrate a low level of job satisfaction while there is a moderate level of work-life balance. However, the results indicated there is a significant difference in the level of job satisfaction and level of work-life balance only for the variable sex. Likewise, findings revealed a significant relationship between job satisfaction and work-life balance. The most challenging for the NSE workers are time management, company policies, dealing with customers, and motivation for the job. The study concludes that job satisfaction influences the work-life balance of the NSE workers. The findings of the study provide valuable insight for manpower agencies in the formulation of a human resource program focused on improving employee satisfaction of the job.